The N@C-60 nuclear spin qubit: Bang-bang decoupling and ultrafast phase gates - Morton, J; Tyryshkin, A; Ardavan, A; Benjamin, S; Porfyrakis, K; Lyon, SA; Briggs, G (2006)
Nuclear spins have been proposed for the embodiment of quantum information and yielded the most complex demonstrations of quantum algorithms to date. However, the weak thermal polarisation of nuclear spins in experimentally accessible conditions has presented a barrier to further scaling. Here, we discuss the benefits of a coupled electron spin to the nuclear spin qubit and demonstrate the ideas using the N-14 nuclear spin in the N@C-60 molecule. In addition to providing a resource for nuclear spin polarisation and detection, the electron spin can be exploited to perform ultrafast nuclear spin phase gates, which can in turn be used to dynamically bang-bang decouple the nuclear spin from unwanted interactions.